2003
DOI: 10.1902/jop.2003.74.4.512
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Clinical Attachment Level Recordings: Effects on Prevalence, Extent, and Severity Estimates

Abstract: Examiner variation may preclude comparisons of prevalence estimates between studies. Valid comparisons may be made between studies of extent estimates provided that uniform parameters are used to express the extent of periodontal breakdown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…As regards the latter, it is our opinion that it is extremely hazardous to attempt to ascribe etiology to lesions based on their size. As regards the reliability issue, we have demonstrated that periodontal attachment loss may be diagnosed with a degree of reliability sufficient to warrant the considerations also of the more subtle levels of periodontal destruction (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the latter, it is our opinion that it is extremely hazardous to attempt to ascribe etiology to lesions based on their size. As regards the reliability issue, we have demonstrated that periodontal attachment loss may be diagnosed with a degree of reliability sufficient to warrant the considerations also of the more subtle levels of periodontal destruction (27).…”
Section: Discussionmentioning
confidence: 99%
“…The intraexaminer agreement for clinical attachment loss recordings ranged between 96.5% and 98.8%, while the corresponding interexaminer agreement ranged between 94.6% and 96.0% (27). No attempts were made to assess the reliability of the NUG recordings.…”
Section: Methodsmentioning
confidence: 99%
“…who conducted the clinical examinations in the case–control study was also the gold standard for the training and calibration of the examiners who conducted the screening examinations. Calibration was achieved using test–retest exercises in groups of patients before the screening examination study and repeated test–retest exercises in large groups of adolescents at different intervals during the screening examination (45). The overall percentage agreement for intra‐examiner reliability when assessing CAL ≥ 3 mm in the screening examinations was 99% and the corresponding overall kappa value was 0.85 (45).…”
Section: Methodsmentioning
confidence: 99%
“…Details on the sampling strategy, sample size estimations, participation rates, clinical recordings used to identify the cases, intra-and interexaminer reliability in the recording of CAL, and a detailed description of the clinical periodontal features of cases and controls have been previously published [8,9,11,12]. Ethical approval for the study was obtained from the Ethics Committee of the University of Chile, and informed written consent was provided by each participant or their parents, as appropriate.…”
Section: Methodsmentioning
confidence: 99%